The Ngaha Aina Ngoho Philosophy as the Basis for the Ecological Movement Based on the Local Wisdom of the Mbojo Community - Ahlan (AAI Pengda Riau, 2026)
The philosophy of Ngaha Aina Ngoho is the local wisdom of the Mbojo people, which contains ethical values regarding the balance of human relations with nature, particularly in the context of responsible resource use. This philosophy literally affirms the principle of